An anticodon change switches the identity of E. coli tRNA(mMet) from methionine to threonine. - Schulman, L H (1990)
Recent evidence indicates that the anticodon may often play a crucial role in selection of tRNAs by aminoacyl-tRNA synthetases. In order to quantitate the contribution of the anticodon to discrimination between cognate and noncognate tRNAs by E. coli threonyl-tRNA synthetase, derivatives of the E. coli elongator methionine tRNA (tRNA(mMet)) containing wild type and threonine anticodons have been synthesized in vitro and assayed for threonine acceptor activity. Substitution of the threonine anticodon GGU for the methionine anticodon CAU increased the threonine acceptor activity of tRNA(mMet) by four orders of magnitude while reducing methionine acceptor activity by an even greater amount. These results indicate that the anticodon is the major element which determines the identity of both threonine and methionine tRNAs.